Alternatif Perancangan Dinding Penahan Tanah Tipe Kantilever Untuk Perbaikan Longsoran Lereng Jalan Ruas Jalan Nasional Ampera – Surumana Sulawesi Tengah - Sri Sulka Octavia Saputri K; A. Rumpang Yusuf; Eka Yuniarto (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
In earthquake-prone areas and on slopes at risk of landslides, appropriate slope reinforcement measures are essential. On the Ampera-Surumana road in Central Sulawesi, a landslide of 4.45 meters occurred on a slope opposite a river bend. This landslide was caused by river water seepage, load distribution, and seismic activity that damaged the existing stone masonry retaining wall. This study proposes a cantilever retaining wall as an alternative solution to address the landslide. Slope stability analysis was conducted using GEO5 software and the manual Bishop method. Before loading, the existing slope was safe, with a factor of safety (FS) of 2.29 (unsaturated) and 1.95 (saturated) according to GEO5, and 2.30 (unsaturated) and 1.95 (saturated) per Bishop method. However, after loading, the FS decreased to 1.22 (unsaturated) and 1.10 (saturated) based on GEO5 analysis, and 1.23 (unsaturated) and 1.10 (saturated) according to Bishop method. The analysis indicated a need for soil reinforcement. The stability analysis of the reinforced cantilever retaining wall showed significant increases in FS, with values of 2.59 for overturning, 2.48 for sliding, and 3.38 for bearing capacity using GEO5, and 3.07 for overturning, 2.29 for sliding, and 3.28 for bearing capacity from manual calculations, confirming the effectiveness of the cantilever design in improving slope stability according to SNI 8460:2017.